(untitled) (ModaPalavra e-periódico, 2019)
Marcel Duchamp’s conception of the infrathin provides a vast field of research. It is a fertile ground for propositions about aesthetics, a poetics and a politics in the field of contemporary design and art. Duchamp describes the infrathin as a quality of the sensitive that is in the between, and it is a relational field full of possibilities. Sensitive experiences reorganize the existence to invent a singular’s perception. This study presents an articulation between infrathin’s concept and some design’s projects. Considering the projects and the qualities of our experienceable perception, this study proposes a reflection on how the association between infrathin and design can leverage our creative processes, our being, and living in the world.